Cost-effectiveness analysis of mechanical thrombectomy with stent retriever in the treatment of acute ischemic stroke in Italy. (2nd September 2018) - Ruggeri, Matteo; Basile, Michele; Zini, Andrea; Mangiafico, Salvatore; Agostoni, Elio Clemente; Lobotesis, Kyriakos; Saver, Jeffrey; Coretti, Silvia; Drago, Carlo; Cicchetti, Americo
Abstract: Background: Stroke has a significant disease burden in terms of acute and long-term disability in Italy and throughout the world. Endovascular treatments for the management of a stroke event have been coupled in the past years with the possibility to mechanically remove the occlusion by means of specially designed thrombectomy devices, and their exclusive use showed levels of effectiveness in line with those of the existing pharmacological treatments. Objective: To assess the cost-effectiveness of mechanical thrombectomy (MT) with the Solitaire Revascularization Device (stent retriever) for the treatment of acute ischemic stroke (AIS) in patients with large vessel occlusions (LVOs), comparing MT plus intravenous tissue plasminogen activation (MT plus IV t-PA) vs IV t-PA alone, in Italy. Methods: A Markov model was used to simulate costs and benefits of MT plus IV t-PA and IV t-PA alone over a 5-year time horizon and considering the perspective of the Italian National Health Service (NHS). Results are reported in terms of Incremental Cost Effectiveness Ratio (ICER). Deterministic and probabilistic sensitivity analyses are carried out in order to test the robustness of the results. Results: Total costs of MT plus IV t-PA and IV t-PA alone are equal to €31, 798 and €34, 855, respectively. The MT allows incremental QALYs for 0.77, determining a dominant ICER. The utilities associated to the mRS health states are the parameters with the highest impact on the results. Multiway sensitivity analyses determined a 90% probability of dominance. Conclusions: MT plus IV t-PA for AIS patients with LVO is cost-effective from year 1 through year 3, and cost-saving from year 4 onward in the Italian context, achieving better results, both in terms of efficacy and in terms of resource consumption.